Opinion of Parents about Child Labour and Their Education – A Study - Nengroo, Aasif Hussain; Bhat, Ghulam Muhammad (Journal of Empirical Studies, 2015)
Much research has been done about the determinants of child labour, both at the national and international level but unfortunately very less research has been done about parents’ opinion on child labour and their education. In order to fill this gap we have done a household survey in Kashmir valley and have identified 88 parents whose young blood is working for the fortitude of their family. Our study found that adverse social and economic conditions force parents to engage their children in the labour market, notwithstanding their altruistic attitude towards their children for a while. We also observed that parents expect that it is the government that should play a pivotal role in the education of working children.